2019
DOI: 10.1159/000501096
|View full text |Cite
|
Sign up to set email alerts
|

Association between Growth Differentiation Factor 15 and Non-Dipping Circadian Pattern in Patients with Newly Diagnosed Essential Hypertension

Abstract: Objective: Non-dipper hypertension (HT) confers greater risk compared with dipper HT. Growth differentiation factor 15 (GDF-15) recently emerged as a novel and independent marker of cardiovascular disease, both in diagnostic and prognostic scopes. Our aim was to evaluate the relationship of circadian blood pressure (BP) pattern with serum GDF-15 level in newly diagnosed HT patients without left ventricular hypertrophy. Subjects and Methods: Newly diagnosed non-dipper (n = 66) and dipper (n = 60) HT patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
0
0
1
Order By: Relevance
“…This could explain why our case group presented a high prevalence of hypertension. It has been demonstrated that serum GDF-15 levels are elevated in patients with hypertension, and that GDF-15 levels are positively correlated with nocturnal diastolic blood pressure [ 49 ]. Several studies supported a positive correlation between GDF-15 levels and pulmonary artery pressure, which can be employed to predict pulmonary hypertension [ [50] , [51] , [52] ].…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why our case group presented a high prevalence of hypertension. It has been demonstrated that serum GDF-15 levels are elevated in patients with hypertension, and that GDF-15 levels are positively correlated with nocturnal diastolic blood pressure [ 49 ]. Several studies supported a positive correlation between GDF-15 levels and pulmonary artery pressure, which can be employed to predict pulmonary hypertension [ [50] , [51] , [52] ].…”
Section: Discussionmentioning
confidence: 99%
“…Результаты недавних исследований указывают на то [30], что существует значительная корреляция между артериальной гипертензией и аномальной экспрессией GDF-15, что позволяет предположить, что он участвует в ремоделировании органов, вызванном данным заболеванием. По результатам исследования PIVUS установлено, что чем выше уровень GDF-15, тем более выражены у пациентов ремоделирование миокарда и гипертрофия левого желудочка [25].…”
Section: Gdf-15 и прогрессирование сердечно-сосудистых заболеванийunclassified
“…При цьому, [13] та жорсткістю аорти [14], що за думкою авторів дослідження пояснює тісний зв'язок РФД-15 з ризиком СС подій та розвитком СН на популяційному рівні та у окремих когорт [15]. Крім того, показано, що підвищення рівня РФД-15 тісно корелює з порушеннями циркадного ритму за типом «non-dipper» [16]. Таким чином, показана в нашому дослідженні залежність рівня РФД-15 від досягнення «цільового» рівня АТ може пояснюватись позитивним впливом на гемодинаміку та структурні зміни в серцево-судинній системі внаслідок кращого контролю АТ, як такого, що врешті корелює зі зменшенням ризику СС подій, в тому числі смертності, розвитку СН та ЦД [15].…”
Section: вплив терапії артеріальної гіпертензії в залежності від класunclassified